Prevalence and Characteristic of Superficial Fungal Infection in Denpasar City, Bali, Indonesia - Wirawan, I Gde Nengah Adhilaksman Sunyamurthi; Wijaya, I Made Indra (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University, 2023)
Superficial mycoses are the most common dermatological diseases caused chiefly by dermatophytes. Due to poor hygiene, superficial mycosis is more common in rural areas, yet the disease can also spread in urban areas. This study aims to determine the prevalence of superficial mycoses and compare the characteristics of skin lesions with the results of a microscopic examination of the fungus. According to this study, Pityriasis versicolor (22.2%), Tinea corporis (35.8%), and Tinea cruris (25.3%) were the three most prevalent superficial mycoses. The age distribution revealed that 25.4% of the samples were obtained from children, 37.3% from young adults, 25.4% from middle-aged adults, and 11.9% from old adults. Results from microscopic examination suggest that hyphae were absent in 28.4% of samples suspected of having an infection with superficial mycoses. In this study, the short hyphae of Malassezia and the septate and hyaline hyphae of dermatophytes could be distinguished.